Laser Surface Texturing of Stainless Steel − Effect of Pulse Duration on Texture's Morphology and Frictional Response. Issue 3 (29th November 2018) - Zhang, Junjie; Yang, Dinghuai; Rosenkranz, Andreas; Zhang, Jianguo; Zhao, Liang; Song, Chengwei; Yan, Yongda; Sun, Tao
Abstract : Laser surface texturing is a powerful tool to fabricate functional surface textures, whereby their morphology and cross‐sectional profile greatly depend on laser parameters such as pulse duration and fluence. In this work, the authors fabricate well‐defined groove‐like textures on stainless steel by laser surface texturing using different pulse durations ranging from nano‐ to femtoseconds, while keeping structural parameters such as depth and periodicity fairly constant. By doing so, the influence of the pulse duration on the resulting cross‐sectional profile of the textures and its subsequent impact on the tribological response are assessed. Reciprocating ball‐on‐disk tests and computational fluid dynamic simulations with Abaqus are used to evaluate the tribological performance of the as‐fabricated textures. Their results demonstrate that the use of laser pulses with different pulse durations induce changes in the resulting cross‐sectional profiles with the formation of rims/bulges well as the occurrence of recast phenomena and debris accumulation for nanosecond laser pulses. Decreasing the pulse duration significantly reduces the heat affected zone and the thermal damage, as well as avoided the formation of rims/bulges. Reciprocating ball‐on‐disk tests demonstrated that the differences in the cross‐sectional profiles have a significant influence on friction and wear behavior of the textured surfaces. Abstract : The tribological properties of surface textures fabricated with different laser pulse durations ranging from nano‐ to femtoseconds are investigated. The influence of the pulse duration on the textures' profile and its impact on the tribological response are assessed. Their results demonstrate that laser pulse duration has a significant influence on the topography of surface textures and thus the frictional response.